2020
DOI: 10.1161/hypertensionaha.119.14071
|View full text |Cite
|
Sign up to set email alerts
|

Ang II (Angiotensin II) Conversion to Angiotensin-(1-7) in the Circulation Is POP (Prolyloligopeptidase)-Dependent and ACE2 (Angiotensin-Converting Enzyme 2)-Independent

Abstract: The Ang II (Angiotensin II)-Angiotensin-(1-7) axis of the Renin Angiotensin System encompasses 3 enzymes that form Angiotensin-(1-7) ] directly from Ang II: ACE2 (angiotensin-converting enzyme 2), PRCP (prolylcarboxypeptidase), and POP (prolyloligopeptidase). We investigated their relative contribution to Ang-(1-7) formation in vivo and also ex vivo in serum, lungs, and kidneys using models of genetic ablation coupled with pharmacological inhibitors. In wild-type (WT) mice, infusion of Ang II resulted in a rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
184
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 69 publications
5
184
0
4
Order By: Relevance
“…The latter acts as a vasodilator and has anti-inflammatory and cardioprotective effects. According to animal studies, expression of ACE2 in lung tissues is low under normal conditions [31], but is upregulated during lung injury [32]. In fact, some animal studies [33] and pilot studies in humans [34] have suggested a potential therapeutic role of ACE2 against inflammatory acute lung injury.…”
Section: Ace2 Sars-cov-2 and Diabetesmentioning
confidence: 99%
“…The latter acts as a vasodilator and has anti-inflammatory and cardioprotective effects. According to animal studies, expression of ACE2 in lung tissues is low under normal conditions [31], but is upregulated during lung injury [32]. In fact, some animal studies [33] and pilot studies in humans [34] have suggested a potential therapeutic role of ACE2 against inflammatory acute lung injury.…”
Section: Ace2 Sars-cov-2 and Diabetesmentioning
confidence: 99%
“…This is not surprising, since ACE2 and ACE are different enzymes, and ACE inhibitors have been designed specifically for ACE only. ACE2 is a membranebound enzyme, with very low (soluble) levels in blood [8,9]. The occurrence of sACE2 depends on cleavage of its membrane-anchor by A Disintegrin And Metalloprotease 17 (ADAM17) ( Fig.…”
Section: Renin-angiotensin System (Ras) Blockers and Ace2mentioning
confidence: 99%
“…The kidney has abundant ACE2 in the apical border of the proximal tubule where it colocalizes with ACE(9). The lungs, by contrast, have a low level of ACE2 expression such that the metabolism of angiotensin II and formation of angiotensin 1-7 depends on enzymes other than ACE2, namely POP (25). To determine whether deficiency of kidney ACE alters kidney ACE2 expression we used two different genetic models of ACE ablation.…”
Section: Introductionmentioning
confidence: 99%